2015
DOI: 10.1088/1751-8113/48/13/135301
|View full text |Cite
|
Sign up to set email alerts
|

Quantum steering of multimode Gaussian states by Gaussian measurements: monogamy relations and the Peres conjecture

Abstract: It is a topic of fundamental and practical importance how a quantum correlated state can be reliably distributed through a noisy channel for quantum information processing. The concept of quantum steering recently defined in a rigorous manner is relevant to study it under certain circumstances and we here address quantum steerability of Gaussian states to this aim. In particular, we attempt to reformulate the criterion for Gaussian steering in terms of local and global purities and show that it is sufficient a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…One of the most important application is the oneside device-independent quantum key distribution: Suppose A can steer B by sharing a pair of entangled state, then by using only local measurements and classical communications, B can convince that the sharing quantum state is entangled through the communication between A and B. [16,20] Gaussian state is an important quantum states for continuous variable system which shows various applications, such as quantum communication and quantum-limited techniques for sensing, detection, and imaging. [18,19] Recent studies pointed out that the non-steerable states can be demonstrated to be useless for one-sided device-independent quantum key distribution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the most important application is the oneside device-independent quantum key distribution: Suppose A can steer B by sharing a pair of entangled state, then by using only local measurements and classical communications, B can convince that the sharing quantum state is entangled through the communication between A and B. [16,20] Gaussian state is an important quantum states for continuous variable system which shows various applications, such as quantum communication and quantum-limited techniques for sensing, detection, and imaging. [18,19] Recent studies pointed out that the non-steerable states can be demonstrated to be useless for one-sided device-independent quantum key distribution.…”
Section: Introductionmentioning
confidence: 99%
“…[17] The effective steering relies DOI: 10.1002/andp.201700328 on the entanglement of quantum state, however, not all entangled quantum states have steering. [20][21][22][23][24][25][26] Gaussian steering is the quantum steering for Gaussian states under Gaussian measurement. [16,20] Gaussian state is an important quantum states for continuous variable system which shows various applications, such as quantum communication and quantum-limited techniques for sensing, detection, and imaging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A strict monogamy relation was later found such that if one party has quantum correlation with a certain number parties, (s)he cannot be correlated with the other parties. Such a relation is proved to be true in quantum nonlocality [27] and quantum steering [28], particularly for Gaussian states under Gaussian measurement [29]. However, extended to non-Gaussian measurements, such a strict monogamy may break down even for Gaussian states [30].…”
Section: Introductionmentioning
confidence: 99%